Implementation of Imla Online Learning - Norhidayah Norhidayah; Aulia Mustika Ilmiani; Marsiah Marsiah (Institut Agama Islam Negeri (IAIN) Metro, 2021)
Facing the era of globalization and technological developments lately, the world is faced with a fast flow of information. Therefore, the importanceof information technology and the internet in various fields of life, including the worldof education. This study aims to describe the implementation of imla online learning. This research uses descriptive qualitative research. The object of this research is the student the students of Hasanka boarding school Palangka Raya. This research technique uses observation and interviews. The results showed that the implementation of imla online learning could improve students’ ability to write Arabic. Judging from the learning that has been applied with the progress of each meeting, where students can write correctly or not make mistakes. Judging from the results of the research that there has been an increase in students, let online-based learning continue to be carried out, because with the online learning of imla ‘this makes people who want to learn very easy to obtain, then it will also have a positive impact on smartphone users who is on the rise at this time.